Silicon-carbon negative electrode material, negative electrode and preparation method and application thereof

By covering elemental sulfur on the nano-silicon surface of the negative electrode material of the lithium-ion battery and forming an organic polymer coating on the graphite oxide material, the problem of volume expansion and insufficient conductivity of the silicon negative electrode material during charging and discharging is solved, and a higher first-time Coulomb efficiency and rate performance are achieved.

CN119627078APending Publication Date: 2025-03-14HUNAN CHMM-SUNWARDS NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411801194.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The electrode powder is caused by changes in volume expansion during charging and discharging, and the stable SEI film cannot be produced, resulting in irreversible capacity loss and capacity attenuation. At the same time, its conductivity and diffusion are poor, resulting in lower first-time Coulomb efficiency and poor rate performance.

Method used

By covering a layer of elemental sulfur on the nano-silicon surface and assembling the silicon carbon material on the graphite oxide material, an organic polymer coating layer is formed. The specific steps include grinding and mixing, oxidation treatment, polymer coating, etc.

Benefits of technology

This method can ease volume expansion by generating a modified layer rich in lithium ions, improve lithium ion transmission capabilities, improve first-time Coulomb efficiency and rate performance, and enhance cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627078A_ABST
    Figure CN119627078A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery negative electrode materials, and provides a silicon-carbon negative electrode material, a negative electrode and a preparation method and application thereof. The method comprises the following steps: S1, preparing a silicon material A coated with elemental sulfur; s2, preparing a graphite oxide material B; s3, stirring and dispersing the elemental sulfur coated silicon material A and the graphite oxide material B in a polar solvent and a nonionic dispersant to obtain a mixed solution C; s4, adding a catalyst and a polymerization precursor into the suspension C; and S5, after filtering, washing with a polar solvent and deionized water, and drying to obtain the polymer-coated silicon carbon material negative electrode material. The surface of the nano silicon is coated with elemental sulfur, so that the cycle performance of the silicon negative electrode is improved; a polyamide coating layer formed on the surface of the graphite oxide material B through a catalyst and a polymerization precursor can effectively anchor the silicon nanoparticles on the surface of the graphite material, so that the volume expansion of the silicon nanoparticles in circulation is further reduced, and the circulation stability of the silicon-carbon negative electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery negative electrode materials, and in particular to a silicon-carbon negative electrode material, a negative electrode, and a preparation method and application thereof. Background Art

[0002] In order to reduce dependence on fossil fuels and reduce environmental pollution, electric vehicles have developed rapidly. Lithium-ion batteries have become an ideal energy carrier for digital electronics, electric vehicles and energy storage power stations due to their high energy density, long cycle life and no memory effect. The negative electrode material is one of the four key materials of lithium-ion batteries, which is mainly divided into two categories: carbon materials and non-carbon materials.

[0003] High-capacity negative electrode materials are an important component of the next generation of high-energy-density lithium-ion batteries, and are mainly divided into metal negative electrodes (such as Li) and silicon-based negative electrodes. However, silicon's volume expansion changes during the charge and discharge process cause electrode pulverization, making it impossible to produce a stable SEI film. Continuous consumption of lithium causes a large amount of irreversible capacity loss, which accelerates capacity decay; secondly, silicon has poor conductivity and diffusion, resulting in lower first coulomb efficiency and poor rate performance. Summary of the invention

[0004] The main purpose of the present invention is to provide a silicon-carbon negative electrode material, a negative electrode and a preparation method and application thereof to solve the above-mentioned technical problems.

[0005] To achieve the above-mentioned purpose, the present invention provides a silicon-carbon negative electrode material, comprising a silicon-carbon material and an organic polymer coating layer coating the silicon-carbon material, wherein the carbon material in the silicon-carbon material is an oxidized graphite material, and the silicon material in the silicon-carbon material contains a single sulfur coating layer; the organic polymer coating layer is a polyamide coating layer, and the ratio between the content R of amide functional groups and the content Q of carboxyl functional groups in the organic polymer coating layer satisfies 1.7≤R / Q≤6.0.

[0006] Preferably, the silicon material in the silicon-carbon material is nano-silicon powder, and the mass ratio of nano-silicon powder to elemental sulfur is 10:0.5-3.

[0007] Preferably, the carbon material in the silicon-carbon material is formed by oxidation of natural graphite or artificial graphite, with a particle size of 5-25 μm, and the thickness of the organic polymer coating layer is 5-500 nm.

[0008] Preferably, the polymer precursor of the organic polymer coating layer is one or more of polyetheramine, polyethyleneimine, polyamino acid and dopamine.

[0009] Preferably, the mass ratio of silicon material to carbon material in the silicon-carbon material is 0.5-2:8-11.

[0010] The present invention also provides a method for preparing the silicon-carbon negative electrode material as described in any one of the above items, comprising the steps of:

[0011] S1: After grinding and mixing the silicon material and elemental sulfur, the mixture is kept at 280-320°C for 3-5 hours and at 140-165°C for 3-5 hours in a sealed reaction container, and after cooling to room temperature, the mixture is ground and dispersed to obtain elemental sulfur-coated silicon material A;

[0012] S2: stirring and dispersing the powdered carbon material, adding an oxidant and stirring for reaction, and then washing and drying to obtain graphite oxide material B;

[0013] S3: dispersing the elemental sulfur-coated silicon material A in a polar solvent, adding a non-ionic dispersant, stirring and dispersing, adding the graphite oxide material B, and continuing to stir to obtain a mixed solution C;

[0014] S4: adding a catalyst and a polymer precursor to the suspension C, stirring and dispersing; wherein the catalyst comprises a first catalyst and a second catalyst, the first catalyst is 1-ethyl-(3-dimethylaminopropyl)carbodiimide, the second catalyst is one or both of N-hydroxysuccinimide and N-hydroxysulfosuccinimide, and the polymer precursor is one or more of polyetheramine, polyethyleneimine, polyamino acid, and dopamine; wherein the mass ratio of elemental sulfur-coated silicon material A, nonionic dispersant, graphite oxide material B, polymer precursor, first catalyst, and second catalyst is: 0.5-2: 0.05-0.2: 8-11: 1.5-2.5: 0.15-0.25: 0.25-0.35;

[0015] S5: After filtering the mixed solution containing the catalyst and the polymer precursor, washing with a polar solvent and deionized water and drying, a polymer-coated silicon-carbon material negative electrode material is obtained.

[0016] Preferably, in step S2, the oxidant is one or more of hydrogen peroxide, concentrated nitric acid, concentrated sulfuric acid, concentrated phosphoric acid, potassium permanganate, and potassium dichromate.

[0017] Preferably, the oxidant is hydrogen peroxide, the concentration of hydrogen peroxide is 25-35% by mass, and the mass ratio of carbon material to hydrogen peroxide is 1:4-6.

[0018] Preferably, the polar solvent is one or more of dimethyl sulfoxide, dimethylformamide, acetonitrile, tetrahydrofuran, and N-methylpyrrolidone (NMP) solvents.

[0019] Preferably, the nonionic dispersant may be one or more of the nonionic surfactants known in the art such as aliphatic polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, fatty amine polyoxyethylene ether, polyoxyethylene alkylamide, etc. In order to better disperse the elemental sulfur-coated silicon material, more preferably, the hydrophilic-lipophilic balance value (HLB value) of the nonionic dispersant should satisfy: 1.8≤HLB≤12.8.

[0020] The present invention also provides a negative electrode, which is prepared using the silicon-carbon negative electrode material as described in any one of the above items.

[0021] The present invention also provides a use of the silicon-carbon negative electrode material as described in any one of the above items as a negative electrode material for a lithium-ion battery.

[0022] The silicon-carbon negative electrode material in the present invention is formed by coating a layer of elemental sulfur on the surface of nano-silicon. In the first cycle of the battery assembled with the silicon-carbon material, the elemental sulfur is converted into lithium polysulfide. The lithium polysulfide reacts with the ester electrolyte to generate substances containing Li2CO3, alkyl lithium sulfate (ROSO2Li), LiF, etc. These lithium salts have good lithium ion transmission ability, which can not only alleviate the volume expansion but also improve the lithium ion transmission ability of the silicon negative electrode surface. It can not only reduce the contact between silicon and the electrolyte, inhibit the decomposition of the electrolyte, and improve the first effect; it can also limit the volume expansion of silicon and improve the cycle performance of the silicon negative electrode. In addition, the polyamide coating layer formed on the surface of the graphite oxide material B by the first catalyst, the second catalyst and the polymer precursor can effectively anchor the silicon nanoparticles on the surface of the graphite material, further reduce the volume expansion of the silicon nanoparticles in the cycle, and improve the cycle stability of the silicon-carbon negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings are part of the present invention and are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention, but do not constitute an improper limitation of the present invention. Obviously, the drawings described below are only some embodiments. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the accompanying drawings:

[0024] Figure 1 Schematic diagram of the preparation process of the silicon-carbon negative electrode material in the present invention.

[0025] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0026] The following is a clear and complete description of the technical problems solved by the embodiments of the present invention, the technical solutions adopted, and the technical effects achieved in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other equivalent or obviously modified embodiments obtained by ordinary technicians in this field without creative work fall within the scope of protection of the present invention. The embodiments of the present invention can be concretized in a variety of different ways as defined and covered in the claims.

[0027] It should be noted that in the following description, many specific details are given for ease of understanding, but it is obvious that the present invention can be implemented without these specific details.

[0028] It should be noted that, in the absence of clear limitation or conflict, the various embodiments of the present invention and the technical features therein can be combined with each other to form a technical solution.

[0029] Embodiment 1:

[0030] S1: 1g of nano-silicon and 0.1g of elemental sulfur were mixed evenly in an agate mortar, and then placed in a sealed Teflon-lined reactor. The reactor was kept at 300°C for 4h and 155°C for 4h in a muffle furnace. After cooling to room temperature, it was ground and dispersed in an agate mortar to obtain elemental sulfur-coated silicon material A;

[0031] S2: 10 g of graphite material was dispersed in 100 mL of deionized water by stirring, 50 g of 30% mass dispersed H2O2 was added, stirred for 6 h, then rinsed with deionized water, and dried to obtain graphite oxide material B.

[0032] S3: Disperse 1 g of elemental sulfur-coated silicon material A in 100 mL of dimethylformamide (DMF), add 0.1 g of polyoxyethylene dioleate (Atlas G-2242, HLB=7.5), stir and disperse for 20 min, then add graphite oxide material B, and continue stirring for 20 min to obtain a mixed solution C.

[0033] S4: Add 0.2 g of EDC, 0.3 g of NHS and 2 g of polyetheramine (HUNTSMAN JEFFAMINE, D2000, Mn=2000) into the mixed solution C and stir for 24 h.

[0034] S5: The mixed solution containing the catalyst and the polymer precursor is filtered with dimethylformamide (DMF) and deionized water, and vacuum dried at 140° C. to obtain a polymer-coated silicon-carbon negative electrode material.

[0035] Embodiment 2:

[0036] S1: 1g of nano-silicon and 0.1g of elemental sulfur were mixed evenly in an agate mortar, and then placed in a sealed Teflon-lined reactor. The reactor was kept at 300°C for 4h and 155°C for 4h in a muffle furnace. After cooling to room temperature, it was ground and dispersed in an agate mortar to obtain elemental sulfur-coated silicon material A;

[0037] S2: 10 g of graphite material was dispersed in 100 mL of deionized water by stirring, 50 g of 30% mass dispersed H2O2 was added, stirred for 6 h, then rinsed with deionized water, and dried to obtain graphite oxide material B.

[0038] S3: 1 g of elemental sulfur-coated silicon material A was dispersed in 100 mL of dimethylformamide (DMF), 0.1 g of sorbitan trioleate (Arlacel 85, HLB=1.8) was added, and the mixture was stirred and dispersed for 20 min. Then, graphite oxide material B was added, and stirring was continued for 20 min to obtain a mixed solution C.

[0039] S4: 0.2 g of EDC, 0.3 g of NHS and 2 g of polyetheramine (HUNTSMAN JEFFAMINE, D2000, M n =2000) was added into mixed solution C and stirred for 24 h.

[0040] S5: The mixed solution containing the catalyst and the polymer precursor is filtered with dimethylformamide (DMF) and deionized water, and vacuum dried at 140° C. to obtain a polymer-coated silicon-carbon negative electrode material.

[0041] Embodiment 3:

[0042] S1: 1g of nano-silicon and 0.1g of elemental sulfur were mixed evenly in an agate mortar, and then placed in a sealed Teflon-lined reactor. The reactor was kept at 300°C for 4h and 155°C for 4h in a muffle furnace. After cooling to room temperature, it was ground and dispersed in an agate mortar to obtain elemental sulfur-coated silicon material A;

[0043] S2: 10 g of graphite material was dispersed in 100 mL of deionized water by stirring, 50 g of 30% mass dispersed H2O2 was added, stirred for 6 h, then rinsed with deionized water, and dried to obtain graphite oxide material B.

[0044] S3: 1 g of elemental sulfur-coated silicon material A was dispersed in 100 mL of dimethylformamide (DMF), 0.1 g of propylene glycol fatty acid ester (Emcol PM-50, HLB=4.1) was added, stirred and dispersed for 20 min, and then graphite oxide material B was added, and stirring was continued for 20 min to obtain a mixed solution C.

[0045] S4: 0.2 g of EDC, 0.3 g of NHS and 2 g of polyetheramine (HUNTSMAN JEFFAMINE, D2000, Mn =2000) was added into mixed solution C and stirred for 24 h.

[0046] S5: The mixed solution containing the catalyst and the polymer precursor is filtered with dimethylformamide (DMF) and deionized water, and vacuum dried at 140° C. to obtain a polymer-coated silicon-carbon negative electrode material.

[0047] Embodiment 4:

[0048] S1: 1g of nano-silicon and 0.1g of elemental sulfur were mixed evenly in an agate mortar, and then placed in a sealed Teflon-lined reactor. The reactor was kept at 300°C for 4h and 155°C for 4h in a muffle furnace. After cooling to room temperature, it was ground and dispersed in an agate mortar to obtain elemental sulfur-coated silicon material A;

[0049] S2: 10 g of graphite material was dispersed in 100 mL of deionized water by stirring, 50 g of 30% mass dispersed H2O2 was added, stirred for 6 h, then rinsed with deionized water, and dried to obtain graphite oxide material B.

[0050] S3: Disperse 1 g of elemental sulfur-coated silicon material A in 100 mL of dimethylformamide (DMF), add 0.1 g of polyoxyethylene monolaurate (Atlas G-2127, HLB=12.8), stir and disperse for 20 min, then add graphite oxide material B, and continue stirring for 20 min to obtain a mixed solution C.

[0051] S4: 0.2 g of EDC, 0.3 g of NHS and 2 g of polyetheramine (HUNTSMAN JEFFAMINE, D2000, M n =2000) was added into mixed solution C and stirred for 24 h.

[0052] S5: The mixed solution containing the catalyst and the polymer precursor is filtered with dimethylformamide (DMF) and deionized water, and vacuum dried at 140° C. to obtain a polymer-coated silicon-carbon negative electrode material.

[0053] Embodiment 5:

[0054] S1: 1g of nano-silicon and 0.1g of elemental sulfur were mixed evenly in an agate mortar, and then placed in a sealed Teflon-lined reactor. The reactor was kept at 300°C for 4h and 155°C for 4h in a muffle furnace. After cooling to room temperature, it was ground and dispersed in an agate mortar to obtain elemental sulfur-coated silicon material A;

[0055] S2: 10 g of graphite material was dispersed in 100 mL of deionized water by stirring, 50 g of 30% mass dispersed H2O2 was added, stirred for 6 h, then rinsed with deionized water, and dried to obtain graphite oxide material B.

[0056] S3: Disperse 1 g of elemental sulfur-coated silicon material A in 100 mL of dimethylformamide (DMF), add 0.1 g of polyoxyethylene dioleate (Atlas G-2242, HLB=7.5), stir and disperse for 20 min, then add graphite oxide material B, and continue stirring for 20 min to obtain a mixed solution C.

[0057] S4: Add 0.2 g of EDC, 0.3 g of NHS and 2 g of polylysine (Sigma-Aldrich, P4707) to the mixed solution C and stir for 24 h.

[0058] S5: The mixed solution containing the catalyst and the polymer precursor is filtered with dimethylformamide (DMF) and deionized water, and vacuum dried at 140° C. to obtain a polymer-coated silicon-carbon negative electrode material.

[0059] Embodiment 6:

[0060] S1: 1g of nano-silicon and 0.1g of elemental sulfur were mixed evenly in an agate mortar, and then placed in a sealed Teflon-lined reactor. The reactor was kept at 300°C for 4h and 155°C for 4h in a muffle furnace. After cooling to room temperature, it was ground and dispersed in an agate mortar to obtain elemental sulfur-coated silicon material A;

[0061] S2: 10 g of graphite material was dispersed in 100 mL of deionized water by stirring, 50 g of 30% mass dispersed H2O2 was added, stirred for 6 h, then rinsed with deionized water, and dried to obtain graphite oxide material B.

[0062] S3: Disperse 1 g of elemental sulfur-coated silicon material A in 100 mL of dimethylformamide (DMF), add 0.1 g of polyoxyethylene dioleate (Atlas G-2242, HLB=7.5), stir and disperse for 20 min, then add graphite oxide material B, and continue stirring for 20 min to obtain a mixed solution C.

[0063] S4: Add 0.2 g of EDC, 0.3 g of NHS and 2 g of polyethyleneimine (EPOMIN, SP-018) into the mixed solution C and stir for 24 h.

[0064] S5: The mixed solution containing the catalyst and the polymer precursor is filtered with dimethylformamide (DMF) and deionized water, and vacuum dried at 140° C. to obtain a polymer-coated silicon-carbon negative electrode material.

[0065] Embodiment 7:

[0066] S1: 1g of nano-silicon and 0.1g of elemental sulfur were mixed evenly in an agate mortar, and then placed in a sealed Teflon-lined reactor. The reactor was kept at 300°C for 4h and 155°C for 4h in a muffle furnace. After cooling to room temperature, it was ground and dispersed in an agate mortar to obtain elemental sulfur-coated silicon material A;

[0067] S2: 10 g of graphite material was dispersed in 100 mL of deionized water by stirring, 50 g of 30% mass dispersed H2O2 was added, stirred for 6 h, then rinsed with deionized water, and dried to obtain graphite oxide material B.

[0068] S3: Disperse 1 g of elemental sulfur-coated silicon material A in 100 mL of dimethylformamide (DMF), add 0.1 g of polyoxyethylene dioleate (Atlas G-2242, HLB=7.5), stir and disperse for 20 min, then add graphite oxide material B, and continue stirring for 20 min to obtain a mixed solution C.

[0069] S4: Add 0.2 g of EDC, 0.3 g of NHS and 2 g of dopamine (Sigma-Aldrich, H8502) to the mixed solution C and stir for 24 h.

[0070] S5: The mixed solution containing the catalyst and the polymer precursor is filtered with dimethylformamide (DMF) and deionized water, and vacuum dried at 140° C. to obtain a polymer-coated silicon-carbon negative electrode material.

[0071] Embodiment 8:

[0072] S1: 1g of nano-silicon and 0.1g of elemental sulfur were mixed evenly in an agate mortar, and then placed in a sealed Teflon-lined reactor. The reactor was kept at 300°C for 4h and 155°C for 4h in a muffle furnace. After cooling to room temperature, it was ground and dispersed in an agate mortar to obtain elemental sulfur-coated silicon material A;

[0073] S2: 10 g of graphite material was dispersed in 100 mL of deionized water by stirring, 50 g of 30% mass dispersed H2O2 was added, stirred for 6 h, then rinsed with deionized water, and dried to obtain graphite oxide material B.

[0074] S3: Disperse 1 g of elemental sulfur-coated silicon material A in 100 mL of dimethylformamide (DMF), add 0.1 g of polyoxyethylene dioleate (Atlas G-2242, HLB=7.5), stir and disperse for 20 min, then add graphite oxide material B, and continue stirring for 20 min to obtain a mixed solution C.

[0075] S4: Add 0.2 g of EDC, 0.3 g of sulfo-NHS and 2 g of polyetheramine (HUNTSMAN JEFFAMINE, D2000, Mn=2000) into the mixed solution C and stir for 24 h.

[0076] S5: The mixed solution containing the catalyst and the polymer precursor is filtered with dimethylformamide (DMF) and deionized water, and vacuum dried at 140° C. to obtain a polymer-coated silicon-carbon negative electrode material.

[0077] Comparative Example 1:

[0078] 10 g of graphite material was dispersed in 100 mL of deionized water by stirring, 50 g of 30% mass dispersed H2O2 was added, stirred for 6 h, rinsed with deionized water, and dried to obtain graphite oxide material B, which was directly used as the negative electrode material.

[0079] Comparative Example 2:

[0080] The difference between this comparative example and Example 1 is that nano-silicon is used in S3 to replace elemental sulfur-coated silicon, and the remaining steps and parameters are consistent with the example.

[0081] Comparative Example 3:

[0082] The difference between this comparative example and Example 1 is that the elemental sulfur-coated silicon material A obtained by grinding and dispersion in S1 is directly used as the negative electrode material.

[0083] Comparative Example 4:

[0084] The difference between this comparative example and Example 1 is that the suspension C obtained in S3 is filtered with dimethylformamide (DMF) and deionized water, vacuum dried at 140° C., and then ground and dispersed as the negative electrode material.

[0085] Comparative Example 5:

[0086] The difference between this comparative example and Example 1 is that no EDC is added during the stirring process in step S4, and the remaining steps and parameters are consistent with the example.

[0087] Comparative Example 6:

[0088] The difference between this comparative example and Example 1 is that no NHS is added during the stirring process in step S4, and the remaining steps and parameters are consistent with the example.

[0089] Comparative Example 7:

[0090] The difference between this comparative example and Example 1 is that EDC and NHS are not added during the stirring process in step S4, and the remaining steps and parameters are consistent with the example.

[0091] Comparative Example 8:

[0092] The difference between this comparative example and Example 1 is that in step S3, polyoxyethylene dioleate (Atlas G-2242, HLB=7.5) is replaced by polyoxyethylene sorbitan monolaurate (Tween 21, HLB=13.3), and the remaining steps and parameters are consistent with the example.

[0093] Comparative Example 9:

[0094] The difference between this comparative example and Example 1 is that in step S3, polyoxyethylene dioleate (Atlas G-2242, HLB=7.5) is replaced by polyoxyethylene monostearate (Myrj 49, HLB=15.0), and the remaining steps and parameters are consistent with the example.

[0095] Comparative Example 10:

[0096] The difference between this comparative example and Example 1 is that the polyetheramine in step S4 is replaced by (HUNTSMAN JEFFAMINE, SD-2001, M n =2000) The remaining steps and parameters are consistent with those in the embodiment.

[0097] Comparative Example 11:

[0098] The difference between this comparative example and Example 1 is that the polyetheramine in step S4 is replaced by (HUNTSMAN JEFFAMINE, D-205, M n =230) The remaining steps and parameters are consistent with those in the embodiment.

[0099] The silicon-carbon materials in Examples 1 to 8 and Comparative Examples 1 to 11 were used as negative electrode active materials, respectively, and were mixed with a conductive agent, styrene-butadiene emulsion (SBR), and carboxymethyl cellulose (CMC) at a mass ratio of 95:1:2.5:1.5 and then coated on a copper foil, and then the electrode was placed at 105°C for vacuum drying for 24 hours; button cells were assembled in a glove box. The electrolyte in the electrolyte was LiPF6 with a concentration of 1M, and the solvent was composed of dimethyl carbonate, ethylene carbonate, and ethyl methyl carbonate in a volume ratio of 1:1:1. The counter electrode was a lithium sheet, and the first coulombic efficiency, rate performance, and cycle performance tests were carried out. The test conditions were as follows, and the results are shown in Table 1.

[0100] The following describes the testing methods for various performance parameters of the silicon-carbon negative electrode material of the present application.

[0101] X-ray photoelectron spectroscopy (XPS) test: Take an appropriate amount of sample and press it into a sample plate. Place the sample in the sample chamber of the VGScienta R3000 instrument and -10 Under ultra-high vacuum conditions of 100 mbar, the test was carried out using a monochromatic Al (Kα) X-ray source with an energy of 1486.6 eV. XPS data were processed using Avantage software to analyze the composition of the surface of the silicon-carbon negative electrode material. The percentage of OC=O species (carboxyl functional group) in the sample C1s spectrum was recorded as Q, and the percentage of NC=O species (amide functional group) in the C1s spectrum was recorded as R. Under normal coating conditions, the R / Q value is used to measure the effect of polymer coating on the surface of the silicon-carbon negative electrode material.

[0102] In order to form a coating layer rich in inorganic and organic lithium salts on the surface of silicon nanoparticles, the assembled button cells were cycled for 3 cycles in the voltage range of 1.5 to 3.0 V before the first coulombic efficiency, rate performance and cycle tests were performed.

[0103] First coulombic efficiency test: first discharge at a current of 0.2mA to 0.01V, let it stand for 10min, then charge at a rate of 0.1C to 2.00V to test the first coulombic efficiency of graphite.

[0104] Rate performance test: After the material completes the first charge and discharge test, discharge it at a constant current and constant voltage (1C / 0.1C) to 0.01V. After standing for 10 minutes, charge it at a constant current (1C / 0.1C) to 2V, and calculate the capacity at different rates.

[0105] Cyclic performance test: After the material completes the first charge and discharge test, discharge it at a constant current and constant voltage (1C) to 0.2V, and charge it at a constant current (1C) to 1.5V. Cycle it for 800 cycles, and calculate the capacity retention rate at the 500th cycle.

[0106] Table 1 Battery performance data of each sample

[0107]

[0108] It can be seen from the performance data in Table 1 that the overall performance of the silicon-carbon negative electrode material prepared by the present invention is better than that of the silicon-carbon negative electrode materials prepared by Comparative Examples 1 to 11, and the specific analysis is as follows.

[0109] From the comparison between Examples 1 to 4 and Comparative Examples 8 to 9, it can be seen that in the preparation process of the silicon-carbon negative electrode, the dispersion of nano-silicon needs to control the HLB value of the non-ionic dispersant. An excessively large HLB value of the non-ionic dispersant is not conducive to the uniform dispersion of nano-silicon in DMF. Undispersed uniform nano-silicon particles have continuous volume expansion during the cycle, thereby affecting the cycle performance of the silicon-carbon negative electrode.

[0110] From the comparison between Example 1 and Comparative Examples 5 to 7, it can be seen that the coating process of the negative electrode material depends on the synergistic effect of EDC and NHS catalysts, and polyetheramine can achieve stable coating under the conditions of the catalyst, thereby improving the cycle and first effect of the negative electrode material.

[0111] From the comparison between Example 8 and Comparative Examples 5 to 7, it can be seen that in the negative electrode material coating process, sulfo-NHS can be used in combination with EDC catalyst to achieve a coating effect similar to that of NHS.

[0112] It can be seen from Example 1 and Examples 5 to 7 that under the synergistic catalysis of EDC and NHS, stable coating with active amino functional groups can be achieved, and the coated negative electrode material has excellent cycle stability, high first efficiency and rate performance.

[0113] From the comparison between Example 1 and Comparative Examples 10-11, it can be seen that the activity of the amino group in the polymer precursor will significantly affect the polyamide coating layer formed on the surface. The polymer precursor with terminal amino groups has higher reaction activity under the condition of a catalyst and can provide a more stable and uniform polyamide coating layer.

[0114] The organic polymer-coated silicon-carbon negative electrode material of the present invention forms a sulfur-containing modified layer on the nano-silicon material, and disperses the nano-silicon material of the sulfur-containing modified layer on the surface of the graphite oxide material under the action of a non-ionic dispersant. In the first few cycles of the assembled button battery, the sulfur element on the surface of the nano-silicon is converted into lithium polysulfide, and the lithium polysulfide reacts with the solvent of the ester electrolyte to generate Li- and S-rich compounds that are uniformly coated on the surface of the nano-silicon. In this way, a modified layer with good lithium ion transmission ability is prepared in situ on the surface of the nano-silicon. The modified layer can not only limit volume expansion, but also promote lithium ion transmission, and can well improve the electrochemical performance of the nano-silicon.

[0115] In addition, the polymer precursor containing active amino groups is anchored on the surface of graphite oxide material through the sulfur-containing modified layer of the polyamide coating layer formed under the condition of catalyst, further alleviating the volume expansion of the nano-silicon negative electrode material during the cycle. At the same time, the formed polymer acts as SEI, effectively hindering the transfer of electrons from the negative electrode material to the electrolyte and inhibiting the decomposition of the electrolyte. The strong adsorption between lithium ions and polymers enhances the desolvation ability of SEI, thereby improving the rate performance of the negative electrode.

[0116] The embodiments described above are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.

Claims

1. A silicon-carbon negative electrode material, comprising a silicon-carbon material and an organic polymer coating layer coating the silicon-carbon material, wherein the carbon material in the silicon-carbon material is an oxidized graphite material; characterized in that: The silicon material in the silicon-carbon material contains a single sulfur coating layer, the organic polymer coating layer is a polyamide coating layer, and the ratio between the content R of amide functional groups and the content Q of carboxyl functional groups in the organic polymer coating layer satisfies 1.7≤R / Q≤6.

0.

2. The silicon-carbon negative electrode material according to claim 1, characterized in that: The silicon material in the silicon-carbon material is nano silicon powder, and the mass ratio of the nano silicon powder to elemental sulfur is 10:0.5-3.

3. The silicon-carbon negative electrode material according to claim 1, characterized in that: The carbon material in the silicon-carbon material is formed by oxidation of natural graphite or artificial graphite, with a particle size of 5-25 μm, and the thickness of the organic polymer coating layer is 5-500 nm.

4. The silicon-carbon negative electrode material according to claim 1, characterized in that: The polymer precursor of the organic polymer coating layer is one or more of polyetheramine, polyethyleneimine, polyamino acid and dopamine.

5. The silicon-carbon negative electrode material according to claim 1, characterized in that: The mass ratio of silicon material to carbon material in the silicon-carbon material is 0.5-2:8-11.

6. A method for preparing a silicon-carbon negative electrode material according to any one of claims 1 to 5, characterized in that: Includes steps: S1: After grinding and mixing the silicon material and elemental sulfur, the mixture is kept at 280-320°C for 3-5 hours and at 140-165°C for 3-5 hours in a sealed reaction container, and after cooling to room temperature, the mixture is ground and dispersed to obtain elemental sulfur-coated silicon material A; S2: stirring and dispersing the powdered carbon material, adding an oxidant and stirring for reaction, and then washing and drying to obtain graphite oxide material B; S3: dispersing the elemental sulfur-coated silicon material A in a polar solvent, adding a non-ionic dispersant, stirring and dispersing, adding the graphite oxide material B, and continuing to stir to obtain a mixed solution C; S4: adding a catalyst and a polymer precursor to the suspension C, stirring and dispersing; wherein the catalyst comprises a first catalyst and a second catalyst, the first catalyst is 1-ethyl-(3-dimethylaminopropyl)carbodiimide, the second catalyst is one or both of N-hydroxysuccinimide and N-hydroxysulfosuccinimide, and the polymer precursor is one or more of polyetheramine, polyethyleneimine, polyamino acid, and dopamine; wherein the mass ratio of elemental sulfur-coated silicon material A, nonionic dispersant, graphite oxide material B, polymer precursor, first catalyst, and second catalyst is: 0.5-2: 0.05-0.2: 8-11: 1.5-2.5: 0.15-0.25: 0.25-0.35; S5: After filtering the mixed solution containing the catalyst and the polymer precursor, washing with a polar solvent and deionized water and drying, a polymer-coated silicon-carbon material negative electrode material is obtained.

7. The method for preparing the silicon-carbon negative electrode material according to claim 6, characterized in that: In step S2, the oxidant is one or more of hydrogen peroxide, concentrated nitric acid, concentrated sulfuric acid, concentrated phosphoric acid, potassium permanganate, and potassium dichromate.

8. The method for preparing the silicon-carbon negative electrode material according to claim 6, characterized in that: The polar solvent is one or more of dimethyl sulfoxide, dimethylformamide, acetonitrile, tetrahydrofuran, and N-methylpyrrolidone (NMP) solvents; the non-ionic dispersant is one or more of the non-ionic surfactants of aliphatic polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, fatty amine polyoxyethylene ether, and polyoxyethylene alkylamide, and the hydrophile-lipophile balance value HLB of the non-ionic surfactant satisfies 1.8≤HLB≤12.

8.

9. A negative electrode, characterized in that Prepared using the silicon-carbon negative electrode material as described in any one of claims 1-5.

10. Use of the silicon-carbon negative electrode material as claimed in any one of claims 1 to 5 as a negative electrode material for a lithium-ion battery.